2008
DOI: 10.5739/isfp.2008.617
|View full text |Cite
|
Sign up to set email alerts
|

Load Sensing With Active Regeneration System

Abstract: The paper introduces a novel system design of fluid power systems which improves the control and energy use for multiple actuators systems with particular focus on mobile applications such excavators, loaders, tractors. The system hereinafter described is based on a new patented technology [1], the "Load Sensing with Active Regeneration System". The main idea is to overcome one of the main drawbacks of multiple actuators conventional Load Sensing Systems: while the higher actuator load drives the pump delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A prediction of the consumed energy by a pressure compensated pump in a valve-controlled circuit, to perform the same pattern of motion, was performed. The power is calculated by multiplying the flow to pressure value of the pressure compensated pump which resulted in 183.6 W. In a valve-controlled hydraulic circuit equipped with load sensing pump, when the load is assistive, the cylinder is uncontrollable [7]. Assuming that in the future the uncontrollability issues using load sensing pump for assistive loads is solved, the theoretical studies have indicated that the energy required to produce the same pattern of motion in the same load condition is 10% higher than the proposed circuit.…”
Section: Further Discussionmentioning
confidence: 99%
“…A prediction of the consumed energy by a pressure compensated pump in a valve-controlled circuit, to perform the same pattern of motion, was performed. The power is calculated by multiplying the flow to pressure value of the pressure compensated pump which resulted in 183.6 W. In a valve-controlled hydraulic circuit equipped with load sensing pump, when the load is assistive, the cylinder is uncontrollable [7]. Assuming that in the future the uncontrollability issues using load sensing pump for assistive loads is solved, the theoretical studies have indicated that the energy required to produce the same pattern of motion in the same load condition is 10% higher than the proposed circuit.…”
Section: Further Discussionmentioning
confidence: 99%